The first record of Asymphylodora progenetica (Trematoda, Monorchiidae) in Ukraine - Kudlai, O.S. (Вестник зоологии, 2010)
The trematode Asymphylodora progenetica Serkova et Bychovskii, 1940 was found in freshwater mollusks Bithynia tentaculata (Linnaeus, 1758) collected from the Kalmius River (near the city of Donetsk) in Ukraine. This species was recorded for the first time in Ukraine. Previously unknown encysted metacercariae and all detected stages of development are described and figured.